Detection of nonpermitted food color metanil yellow in turmeric: A threat to the public health and Ayurvedic drug industry - Abhineet Verma; Satyen Saha; Shobha K Bhat (Wolters Kluwer Medknow Publications, 2022)
Introduction: The food products available in the market today are made attractive by adding food colors. Fruits, vegetables, spices, sweets, and even the commonest drugs used as medicine in day-to-day life are adulterated with nonpermitted colors. Haridra or turmeric is the most popularly used Vishaharadravya/antitoxic drug which is taken internally almost every day both in diet and as medicine. Metanil yellow (MY) is a "nonpermitted" food colorant used extensively as an adulterant in different spices, especially turmeric. Though the quantity of intake would be small, when taken continuously, it may lead to several adverse life-threatening effects in humans. Methods: 20 different samples of Haridra (Turmeric) were collected randomly from markets in and around Varanasi. The presence of nonpermitted food color-MY in these turmeric samples was first tested with preliminary color test followed by ultraviolet-visible spectroscopic studies. The color change and change in absorption spectra have been used to identify the contaminated samples. Results and Conclusion: Two out of twenty samples of Haridra were found to be adulterated with MY. Food adulteration in daily diet is a matter of great concern and is a strong cause for Garavisha. Mass awareness has to be raised on the issue. Our results suggest that special care has to be taken by the turmeric-based Ayurveda manufacturers to avoid the use of such contaminated turmeric.